Eastern influences of the figure of Marcel Proust and precedents to a comparison between À la recherche du temps perdu and Buddhism - Nava Gutiérrez, David (ENDOXA, 2018)
The present study looks for influences from the East in the figure of Marcel Proust. Specifically, from the philosophy that is born from the sermons of Siddhartha Gotama known worldwide as buddhism. After the publication of several articles by some commentators of À la recherche du temps perdu in which it is said that Proust and Buddha have common features, we wanted to focus on the life and work of Proust and to confirm whether the French writer was indeed influenced by these exotic truths and to culminate his work, like Buddha, in an Enlightenment. We will also bring together here the work of these Proustian commentators, since they have not previously been grouped together in a single investigation, just as their proposals on this subject have never been evaluated.